1997
DOI: 10.1266/ggs.72.173
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and interspecific hybridization among natural populations of zoysiagrasses detected by RFLP analyses of chloroplast and nuclear DNA.

Abstract: Genetic variations among 17 accessions of zoysiagrasses collected from natural populations in Japan were investigated by RFLP analyses of chloroplast DNA (cpDNA) and nuclear DNA. These accessions were classified into five species based on morphological characteristics: Zoysia japonica, Z. matrella, Z. tenuifolia, Z. sinica, and Z. macrostachya. On the basis of eight kinds of RFLPs in cpDNAs detected across accessions, six chloroplast genome types (types A-F) were identified. Although type-A cpDNA was shared by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 17 publications
(15 reference statements)
1
36
0
Order By: Relevance
“…Three species of zoysiagrass, Z. japonica , Z. matrella and Z. tenuifolia , can be used to generate interspecific hybrids in all combinations (Forbs, 1952), and it appears that based on morphological observation, many naturally occurring interspecific hybrids can be found in several ecotypes (Fukuoka, 2000). This assumption is also likely to apply to zoysiagrass following both genetic and phylogenetic analysis of zoysiagrass collections in Japan (Yaneshita et al ., 1997). In our study, two accessions, ‘Taketomikaiji 2’ and ‘Katsuren 1–1’, indicated a close relationship to Z. tenuifolia accessions, although their morphological characters differed considerably from Z. matrella and Z. sinica var.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three species of zoysiagrass, Z. japonica , Z. matrella and Z. tenuifolia , can be used to generate interspecific hybrids in all combinations (Forbs, 1952), and it appears that based on morphological observation, many naturally occurring interspecific hybrids can be found in several ecotypes (Fukuoka, 2000). This assumption is also likely to apply to zoysiagrass following both genetic and phylogenetic analysis of zoysiagrass collections in Japan (Yaneshita et al ., 1997). In our study, two accessions, ‘Taketomikaiji 2’ and ‘Katsuren 1–1’, indicated a close relationship to Z. tenuifolia accessions, although their morphological characters differed considerably from Z. matrella and Z. sinica var.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional varietal identification of zoysiagrass has been performed primarily by examining morphological characteristics; however, this is often difficult with closely related cultivars (Yaneshita et al ., 1997). In addition, the ease with which it propagates vegetatively adds an additional burden with regard to variety protection.…”
Section: Introductionmentioning
confidence: 99%
“…2006). Yaneshita et al . (1997) showed that five species of Zoysia could be classified into six haplotypes based on eight RFLP in cpDNA.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical and molecular markers have been used to enhance understanding of plant population genetic structure (Soltis et al, 1992). Among several efficient methods for revealing genetic variability within and among plant populations, some of the most widely applied are isozyme electrophoresis (Hamrick and Allard, 1972;Hamrick and Godt, 1990), random amplified DNA polymorphism -RAPDs - (Wolff and Peters-van Rijn, 1993;Wachira et al, 1995;Brummer et al, 1995;Swoboda and Bhalla, 1997;Palacios and Gonzalez-Candelas, 1997), and restriction fragment length polymorphisms -RFLPs - (Keim et al, 1989;Hong et al, 1993;Yanesita et al, 1997). In the genus Prosopis, previous isoenzymatic studies in some Algarobia Section species have shown low differentiation among species and populations coupled with high variability within populations (Saidman, 1985(Saidman, , 1986(Saidman, , 1990(Saidman, , 1993Saidman and Vilardi, 1987;Verga, 1995).…”
Section: Introductionmentioning
confidence: 99%